Synthesis and biological evaluation of tert-butyl ester and ethyl ester prodrugs of L-γ-methyleneglutamic acid amides for cancer. (15th January 2023) - Khan, Md Imdadul H.; Mahdi, Fakhri; Penfornis, Patrice; Akins, Nicholas S.; Hossain, Md Imran; Kim, Seong Jong; Sulochana, Suresh P.; Adam, Amna T.; Tran, Tristan D.; Tan, Chalet; Paolo Claudio, Pier; Paris, Jason J.; et al.
Graphical abstract: Abstract: In cancer cells, glutaminolysis is the primary source of biosynthetic precursors. Recent efforts to develop amino acid analogues to inhibit glutamine metabolism in cancer have been extensive. Our lab recently discovered many L -γ-methyleneglutamic acid amides that were shown to be as efficacious as tamoxifen or olaparib in inhibiting the cell growth of MCF-7, SK-BR-3, and MDA-MB-231 breast cancer cells after 24 or 72 h of treatment. None of these compounds inhibited the cell growth of nonmalignant MCF-10A breast cells. These L -γ-methyleneglutamic acid amides hold promise as novel therapeutics for the treatment of multiple subtypes of breast cancer. Herein, we report our synthesis and evaluation of two series of tert -butyl ester and ethyl ester prodrugs of these L -γ-methyleneglutamic acid amides and the cyclic metabolite and its tert -butyl esters and ethyl esters on the three breast cancer cell lines MCF-7, SK-BR-3, and MDA-MB-231 and the nonmalignant MCF-10A breast cell line. These esters were found to suppress the growth of the breast cancer cells, but they were less potent compared to the L - γ -methyleneglutamic acid amides. Pharmacokinetic (PK) studies were carried out on the lead L - γ -methyleneglutamic acid amide to establish tissue-specific distribution and other PK parameters. Notably, this lead compound showed moderate exposure to the brain with a half-life of 0.74 h and good tissue distribution, such as in the kidney and liver. Therefore, the L -γ-methyleneglutamic acid amides were then tested on glioblastoma cell lines BNC3 and BNC6 and head and neck cancer cell lines HN30 and HN31. They were found to effectively suppress the growth of these cancer cell lines after 24 or 72 h of treatment in a concentration-dependent manner. These results suggest broad applications of the L - γ -methyleneglutamic acid amides in anticancer therapy.